The Influence of Teamwork Towards Employee Performance in Front Office Department at JW Marriott Medan - Vanessa Eveline; Hengky Kosasih; Tina Linda (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
In hospitality industry, working in a team necessitates a high level of interaction among coworkers. It has been suggested that cooperation contributes to great employee performance because one coworker may have unique competencies, abilities, and expertise that others do not, yet which are necessary for performing a certain task. Therefore, this research is done in order to measure the influence of teamwork towards the employee performance at JW Marriott, Medan. Employee job performance can only be achieved at its best when all the working elements of the organization perform together. Teamwork has been considered as one of the most desired attributes, which an employer wishes to have in modern day organization. The methods or instruments which are used in order to measure this research are quantitative method, deductive approach, descriptive and causal research. In addition, the selection of samples that the writer use in this research is using census sampling by using 30 employees in front office. Besides that, the methods which are used to collect the data are primary and secondary. The results are done through the tests which are research instruments, descriptive statistics, classical assumption test, coefficient of determination (adjusted R2) and hypothesis test. By using these tests, it show that teamwork simultaneously have the influence towards employee performance at JW Marriott, Medan. The writer provides some recommendations which are important for the industry to implement.